‘Out of Poland, Not to Israel, but Out of Poland’: Factors Influencing the Decision to Leave Poland after March 1968: On the Basis of Research from the 1970s - Szajda, Marek (Kwartalnik Historyczny, 2022)
In this article the author explores the question of Jews’ emigration from Poland to Israel after the events of the anti-Zionist campaign of 1968. On the basis of émigrés’ accounts recorded in the 1970s, the author has reconstructed the complex mosaic of factors influencing their decision to leave Poland and choose Israel as their final destination. The most important among these factors were: the ‘anti-Zionist campaign’ and anti-Semitism of the period, as well as the resulting sense of alienation and stigmatization; the large number of people leaving the country, in particular those with family ties and relationships; disappointment with communism; and the Warsaw Pact’s invasion of Czechoslovakia.